The Role of Tibb in Integrative Medicine for Diseases of Lifestyle (Bangladesh Journal of Medical Science, 2017)
Integrative Medicine combines the concepts, values and practices of complementary and alternative medicine with conventional medicine in the comprehensive diagnosis and treatment of disease. Integrative Medicine is concerned with preventing disease, health maintenance and healing, rather than merely eliminating symptoms. The persons innate healing abilities are actively supported, and the importance of mind and spiritual nature are recognised. Integrative Medicine values the relationship between the healer and the patient to promote self-help and provides the appropriate education and motivation required for patient empowerment. The complementary arm of Integrative Medicine adopts specific therapeutic techniques such as massage, herbal medicine and aromatherapy, or medical paradigms such as Tibb, Ayurveda, Naturopathy, or Homeopathy. Tibb, also known as Unani-Tibb (Graeco-Arabic) medicine, is the historical forerunner of conventional medicine, so it is an attractive partner. Integrative Medicine has a major role in both treatment of acute ailments, mainly through the conventional arm of treatment, and long-term management of chronic disorders, mainly via the complementary arm. Integrative Medicine addresses the increasingly common disorders of lifestyle such as hypertension, heart disease, diabetes 2, and depression.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.13-20